(untitled) (Journal of Humanities and Social Sciences Research, 2023)
The research aims to prepare mental fitness exercises and apply them to futsal players. It also aims to identify their impact on futsal players’ planned performance. Identifying the preferential method of mental fitness exercises and the method used by coaches in futsal performance planning. Use the experimental method with two experimental and control groups. There were a total of (20) players on the University of Babylon futsal team during the academic year (2022-2023). In two experimental and control groups, the planned positions were determined by futsal football, namely (depth, expansion, support, penetration, and exchange). Videography conducted two trial matches for the University of Babylon futsal team and presented them through a CD to experts and specialists in futsal. In order to evaluate the planned positions through the calendar form prepared for this purpose. The statistical bag SPSS was used to process the results, and the research outperformed the experimental group. Which represented the effectiveness of mental fitness exercises on the control group in the planned performance. One of the recommendations from the research is the need to conduct more studies on mental fitness exercises. This is for all players in different sports and age groups.